Predictors of Radial Artery Hematoma and Outcomes in Patients Undergoing Elective vs Emergency Angiography Angioplasty via Radial Artery Approach (Indus Journal of Bioscience Research, 2025)
Objective: To identify and evaluate the predictors of radial artery hematoma and their associated outcomes in patients undergoing elective and emergency angioplasty via radial artery access at the Department of Cardiology, Hayatabad Medical Complex, Peshawar, from January 2023 to December 2023.Methodology: This retrospective study included 400 patients, with 200 patients in each group (elective and emergency PCI). The data were collected from medical records, including patient demographics, comorbidities, and procedural characteristics. The main outcome measures were radial artery hematoma and RAO, with statistical analyses performed using chi-square tests, independent t-tests, and multivariate logistic regression.Results: The incidence of radial artery hematoma was 10% in the elective PCI group and 12% in the emergency PCI group (p = 0.49). The RAO incidence was 8% in the elective group and 10% in the emergency group (p = 0.55). Female gender (OR = 1.72, p = 0.03), radial artery spasms (OR = 2.47, p = 0.01), and manual hemostasis (OR = 1.94, p = 0.05) were significant predictors of complications. The time to hemostasis was positively correlated with increased risk (OR = 1.01, p = 0.04).Conclusion: This study confirms that female gender, radial artery spasms, manual hemostasis, and time to hemostasis are key predictors of radial artery complications. Both elective and emergency PCI procedures via radial artery access show similar complication rates, emphasizing the need for proper procedural management.